Mechatronic Integrated Devices Produced by Laser Direct Structuring on Powder-Coated Aluminum Substrates - Kuhn, Thomas; Krügelstein, Andreas; Franke, Jörg (Proceedings of 39th International Spring Seminar on Electronics Technology (ISSE 2016), 2016)
The present study aims to display new potentials for Mechatronic Integrated Devices (MID) by using a powder coating system (PCS) that enables the laser direct structuring process (LDS) on metal-based substrates. Therefore, in a first step, relevant process parameters for the production of MID based on powder-coated aluminum plates were identified. Afterwards, comparative investigations between powder-coated specimen and conventional thermoplastic LDS-MID using liquid crystal polymer (LCP) and thermally conductive polyamide (PA mXD6) as substrate material were executed. The results show clear advantages of the powder-coated parts regarding current carrying capacity of circuit traces. Furthermore, the mechanical characterization of the different specimen indicates considerably higher adhesion strength between metallization and powder coating than between metallization and the investigated thermoplastic materials.
Keywords: 3D-MID; E|P; LDS; Mechatronic Integrated Devices